Image and graphics technologies and applications : 14th Conference on Image and Graphics Technologies and Applications, IGTA 2019, Beijing, China, April 19-20, 2019, revised selected papers /: 14th Conference on Image and Graphics Technologies and Applications, IGTA 2019, Beijing, China, April 19-20, 2019, revised selected papers. ([2019]) - Unknown
No abstract available